Clinical and public health utility of Mycobacterium tuberculosis whole genome sequencing - Kizny Gordon, Alice; Marais, Ben; Walker, Timothy M.; Sintchenko, Vitali (International journal of infectious diseases, 2021)
•WGS has particular value in the diagnosis and management of TB disease.•It can give more rapid and complete information on TB drug-resistance.•The high resolution allows detection of clusters, contamination and mixed infections.•Future goals include culture free & targeted next generation sequencing.•Greatest utility is antimicrobial resistance surveillance in high-burden countries. The World Health Organization (WHO) estimates that around 10 million people develop tuberculosis (TB) every year, with 1.5 million deaths attributed to TB in 2019 (World Health Organization, 2020). The majority of the disease burden occurs in low-income countries, where access to diagnostics and tailored treatment remains problematic. The current COVID-19 pandemic further threatens to impact global TB control by diverting resources, reducing notifications and hence significantly increasing deaths attributable to TB (World Health Organization, 2020). Whole genome sequencing (WGS) is becoming increasingly accessible, and has particular value in the diagnosis and management of TB disease (Cabibbe et al., 2018; Meehan et al., 2019). Not only does it have the potential to give more rapid and complete information on drug-resistance, but the high discriminatory power it offers allows detection of clusters and transmission pathways, as well as likely contamination events, mixed infections and to differentiate between re-infection and relapse with much greater confidence than previous typing methods.